Intellectual property license contracts: reflections on a prospective UNCITRAL project - Tosato, Andrea (University of Cincinnati College of Law, 2017)
IP licenses are the leading lady of the information age. The economic and strategic significance of this contract archetype have grown exponentially over the past 40 years. Under this glaring spotlight, it has become progressively more apparent that the legal framework governing these transactions is ill-suited to the role that they play in the modern digital environment. The applicable norms are scattered throughout diverse areas of the law, rendering a holistic appraisal onerous, and causing both doctrinal underdevelopment and legal uncertainty. Moreover, a comparative analysis of IP licensing regimes across jurisdictions reveals a jarring lack of alignment that severely hinders international transactions. The United Nations Commission on International Trade Law (UNCITRAL) has been contemplating the possibility of a project in this area of the law for over a decade. Though Member States have battled lingering reservations, support has been increasing steadily among practitioners and academics, and is verging on achieving critical mass. This paper provides the necessary theoretical infrastructure for this initiative by expounding its possible scope, content and form. The objective is not to articulate or advocate a single, concrete proposal, but rather to identify the categories of legal issues that UNCITRAL Member States would face in the elaboration of this project and lend color to the types of decision-making processes required to attain consensus solutions. On the basis of this analysis, a strategy to advance this project to its next phase is proposed.